Common Home Remedies Do Not Deter Argentine Ants, Linepithema humile (Hymenoptera: Formicidae), from a Preferred Harborage - Jacob B. Holloway; Daniel R. Suiter; Jerry W. Davis; Wayne A. Gardner (Insects, 2024)
In two laboratory trials, natural products, including freshly picked leaves from spearmint, rosemary, and tansy plants, a water extract from soybean plants, peels from a common cucumber, and 1% peppermint oil in hexane, were placed in a moist harborage preferred by Argentine ants, Linepithema humile (Mayr), and the number of ants entering the harborage after two and four hours was counted. None of the recommended home remedies (tansy, cucumber, or soybean extract) deterred ants from an attractive, moist harborage in either trial, even when the quantity of these treatments was increased 4- to 10-fold. Freshly picked leaves from rosemary and spearmint plants deterred ants from harboring, and the 1% peppermint oil was the most deterrent of all treatments.